The soft law of international law and the implementation of social rights: brief notes on the WHO recommendations and the decisions of the Supreme Federal Court on the pandemic - Borges, Daniel Damásio [UNESP]; Romero, Thiago Giovani [UNESP]; de Paula, Ana Cristina Alves [UNESP] (Centro de Ensino Unificado de Brasilia, 2023)
The purpose of this article is to deal with the relevance of soft law in contemporary international law, proposing a reflection on the possibility of considering soft law as a direct source of public international law. The research intends to revisit the thoughts on the sources of public international law, in order to analyze the role that soft law has been playing in modifying the traditional panorama of sources of international law, highlighting the WHO recommendations and the decisions of the Supreme Federal Court to combat the Covid-19 pandemic. In the construction of the research, the deductive method was used, supported by a specialized literature review. It can be concluded that the recommendations published by the WHO confirm the importance of international standards for dealing with the coronavirus in the world.
O soft law de direito internacional e a concretização dos direitos sociais: breves notas sobre as recomendações da OMS e as decisões do Supremo Tribunal Federal sobre a pandemia*
Keywords: covid-19; public international law; soft law; sources of international law; WHO recommendations